Fluorescently Tagged Poly(methyl methacrylate)s - Fabia Grisi; Rubina Troiano; Donatella Fiore; Patrizia Gazzerro; Mariateresa Lettieri; Vincenzo Venditto; Stefania Pragliola (Molecules)
Plastic pollution is a global problem affecting the environment and, consequently, people’s well-being. Careful and timely end-of-life plastic recycling is certainly a way, albeit a partial one, to remedy the problem. The immediate identification and selection of the different types of plastic materials in the recycling process certainly facilitate its recovery and reuse, allowing the damage caused by plastic emission into the environment to be limited. Recently, new technologies for automatic sorting of plastics based upon fluorescent tagging have been considered. This article reports the synthesis and characterization of fluorescent copolymers of poly(methyl methacrylate) (PMMA) that could be potentially used as fluorescent markers of commercial PMMA. Poly(methylmetacrylate-co-2-(9-carbazolyl)ethyl methacrylate) (P(MMA-co-CEMA)) and poly(methylmetacrylate-co-7-methacryloyloxycoumarin) (P(MMA-co-MAOC)) samples containing a small number of fluorescent units (<4%) were synthesized by free-radical polymerization. All copolymer samples show chemico-physical properties like those of pure PMMA and produce fluorescence emission under 290 nm wavelength excitation. P(MMA-co-CEMA)s and P(MMA-co-MAOC)s were also tested as fluorescent dyes for PMMA identification. The experimental results demonstrate that PMMA/P(MMA-co-CEMA) and PMMA/P(MMA-co-MAOC) blends prepared using 1% by weight of fluorescent copolymer show a homogeneous morphology completely similar to pure PMMA and are still optically active.